Restless legs syndrome and cerebrovascular/cardiovascular events: Systematic review and meta‐analysis. (25th September 2017) - Katsanos, A. H.; Kosmidou, M.; Konitsiotis, S.; Tsivgoulis, G.; Fiolaki, A.; Kyritsis, A. P.; Giannopoulos, S.
Abstract : Objective: We performed a systematic review and meta‐analysis to evaluate the proposed association of restless legs syndrome (RLS) with cerebrovascular/cardiovascular outcomes. Methods: We calculated the corresponding odds ratios on the prevalence of cerebrovascular/cardiovascular risk factors and standardized mean differences on the reported mean age at baseline between RLS patients and controls. We also calculated the corresponding risk ratios and adjusted for potential confounders hazard ratios (HRsadjusted ) on the reported outcomes of interest between RLS patients and controls. Results: We identified 8 eligible studies (644 506 patients, mean age: 60.2 years, 36.2% males; 3.3% with RLS). RLS patients were found to have significantly higher prevalence of hypertension ( P = .002), diabetes ( P = .003) and hyperlipidemia ( P = .010) compared to controls. In the unadjusted analyses of prospective observational studies, RLS patients were found to have significantly higher risk for cerebrovascular ischaemia ( P = .01) and all‐cause mortality ( P = .04) compared to controls during follow‐up, while in the adjusted for potential confounders analyses RLS patients were only found to have a higher risk of all‐cause mortality (HR adjusted=1.52, 95% CI: 1.17‐1.97, P = .002). Conclusions: The present report does not provide evidence for an increased risk of cerebrovascular and cardiovascular events in RLS patients, which highlights the vast presence of confounding factors.